ANALISIS EFISIENSI TEKNIS DAN EKONOMIS PEMBANGKIT LISTRIK TENAGA MIKROHIDRO MENGGUNAKAN HOMER (STUDI KASUS PLTMH PAKEM) - Abilio Faizal, Rifky; Sandi; Nurpulaela, Lela (Universitas Lampung, 2025)
This study analyzes the power efficiency of a Micro-Hydro Power Plant (PLTMH) in the Pakem area using HOMER software. Water demand increased from 7.83 liters/second in 2009 to a projected 15.61 liters/second by 2027, with an average water flow of 1.76 liters/second. The simulation results show that the PLTMH can generate 27,645 kWh per year, with 100% of the energy coming from hydropower. About 6.52% of the energy is used for local needs, while 93.5% is sold to the grid. The PLTMH operates at a capacity factor of 128%, with a low annual operating cost of Rp 92.12. The Net Present Cost (NPC) is recorded at Rp 38,081.26, and the Levelized Cost of Energy (COE) is Rp 0.06613/kWh. The PLTMH in Pakem demonstrates high efficiency both technically and economically, but increasing water demand in the future will require system optimization to maintain sustainable operations.